Model Komunikasi Antar Pribadi Melalui Edukasi Gizi Untuk Peningkatan Pengetahuan Ibu Di Puskesmas Dadok Tunggul Hitam, Padang - Azrimaidaliza Azrimaidaliza; Adisti Qamahadlina Larasati; Hendrizal Usman; Alifya Nurhanif Firman; Kharisma Sekar Wangi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
This educational activity aims to increase mothers' knowledge about nutritious and healthy food by optimizing interpersonal communication in Puskesmas Dadok Tunggul Hitam, Padang City. The activity design is a pre-post intervention without a control group, implemented in late August and early September 2025, targeting 15 mothers. The educational activity, supported by leaflets, includes initial activities in the form of a pre-test, individual education and counseling, discussions, and ends with a post-test. The partner for this activity is Puskesmas Dadok Tunggul Hitam, which plays a role in providing licensing support and data provision. The characteristics of mothers of toddlers are that more than 50% of mothers are aged 30-39 years, have a high school education, and are housewives. The results of the education show an increase in mothers' knowledge after being given individual counseling. The average pre-test score of mothers of toddlers was 7.4 ± 1.183 and increased to 9.4 ± 0.737 in the post-test, with a p-value of 0.0001 (p < 0.05). This indicates that nutrition education through interpersonal communication, which has not been widely used in educational activities, and assisted by leaflets, is effective in increasing mothers' knowledge about nutritious and healthy foods. This increase in knowledge is expected to be implemented in family food consumption behaviors towards a more balanced and healthy nutrition in everyday life, thereby contributing to improving the nutritional status and health of the community.